PENGARUH KEPRIBADIAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI INTERVENING (Studi Pada Universitas Palangka Raya) - Sambung, Roby (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The porpuse of the study was to examine the effect of direct and indirect personality, organizational commitment and Organizational Citizenship Behavior (OCB). This study used the unit of analysis throughout the administration Civil Servants at the University of Palangka Raya, using stratified random sampling obtained 169 administrative employees in the sample. The approach used in this study is a Structural Equation Model (SEM) with the Smart-PLS. The results of this study showed that a significant direct effect on the personality of organizational commitment, and Organizational Citizenship Behavior (OCB). Organizational commitment was not significant effect on Organizational Citizenship Behavior (OCB). Keywords: Personality, Organizational Commitment and Organizational Citizenship Behavior (OCB)